First Amendment Traditionalism - Marc O. DeGirolami (Washington University Law Review, 2020)
Traditionalist constitutional interpretation takes political and cultural practices of long age and duration as constituting the presumptive meaning of the text. This Essay probes traditionalism’s conceptual and normative foundations. It focuses on the Supreme Court’s traditionalist interpretation of the First Amendment to understand the distinctive justifications for traditionalism and the relationship between traditionalism and originalism. The first part of the Essay identifies and describes traditionalism in some of the Court’s Speech and Religion Clause jurisprudence, highlighting its salience in the Court’s recent Establishment Clause doctrine. Part II develops two justifications for traditionalism: “interpretive” and “democratic-populist.” The interpretive justification is that enduring practices presumptively inform the meaning of the words that they instantiate. Generally speaking, we do what we mean, and we mean what we do. The democratic-populist justification is that in a democracy, people who engage in practices consistently and over many years in the belief that those practices are constitutional have endowed those practices with political legitimacy. Courts owe the people’s enduring practices substantial deference as presumptively constitutional. The populist element in this justification is that traditionalism is a defensive interpretive method against what abstract principle in the hands of elite actors has wrought: intolerance, the corrosion of lived experience, and the distortion of text to mirror a particular class of contemporary moral and political views. In Part III, this Essay compares traditionalism with originalism, reaching two conclusions. First, traditionalism’s reliance on practices as presumptively constitutive of constitutional meaning is most distant from originalist theories that rely on abstract principle as constituting the meaning of text and that reject practice-based evidence as the equivalent of irrelevant “expected applications.” It is closest to varieties of originalism that read text concretely. Yet traditionalist judges are not engaged in making guesses about “expected applications,” but in making decisions about retrospective applications—drawing on old and enduring practices either to include within, or exclude from, a tradition the specific practice under review. Second, the Essay investigates the connection between so-called “original law” theories of originalism and traditionalism. Original law theorists argue that originalism is “our law” as a sociological and cultural fact. But traditionalism may be more “our law” than originalism in some areas within the First Amendment and outside it. If the positivist defense of originalism truly counts as a justification for any theory of constitutional interpretation (an issue on which this Essay takes no position), then it may support traditionalism as much as originalism.
Keywords: Traditionalism; Originalism; Interpretive methods; First amendment; Establishment clause; Speech and religion clause